2003
DOI: 10.1074/jbc.m307660200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Intracellular β1-2 Mannan Is a Virulence Factor in Leishmania Parasites

Abstract: The protozoan parasite Leishmania mexicana proliferates within macrophage phagolysosomes in the mammalian host. In this study we provide evidence that a novel class of intracellular ␤1-2 mannan oligosaccharides is important for parasite survival in host macrophages. Mannan (degree of polymerization 4 -40) is expressed at low levels in non-pathogenic promastigote stages but constitutes 80 and 90% of the cellular carbohydrate in the two developmental stages that infect macrophages, non-dividing promastigotes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
108
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 38 publications
6
108
1
1
Order By: Relevance
“…Also lost was the newly discovered ␤1-2 mannan, considered important in protection from stress. It has been suggested that the failure of the GDP-MP mutants to accumulate ␤1-2 mannan may account to a large extent for their lack of survival in vivo (22). The ⌬GDP-MP parasites were viable in cell-free culture but were unable to survive in macrophages or mice, making it a very attractive target for anti-Leishmania drug design.…”
Section: Discussionmentioning
confidence: 99%
“…Also lost was the newly discovered ␤1-2 mannan, considered important in protection from stress. It has been suggested that the failure of the GDP-MP mutants to accumulate ␤1-2 mannan may account to a large extent for their lack of survival in vivo (22). The ⌬GDP-MP parasites were viable in cell-free culture but were unable to survive in macrophages or mice, making it a very attractive target for anti-Leishmania drug design.…”
Section: Discussionmentioning
confidence: 99%
“…Leishmania lack classic carbohydrate reserves, such as glycogen or starch, but synthesize a unique class of oligosaccharides composed of linear chains of ␤-1,2-linked mannose (Man) (5)(6)(7)(8). Leishmania ␤-1,2-mannan clearly functions as a dynamic reserve material and accumulates to millimolar concentrations in infective promastigote and intracellular amastigote stages (8).…”
mentioning
confidence: 99%
“…Leishmania ␤-1,2-mannan clearly functions as a dynamic reserve material and accumulates to millimolar concentrations in infective promastigote and intracellular amastigote stages (8). Mannan also accumulates in parasites subjected to physiological stresses encountered in the macrophage (8), suggesting that it might be important for intracellular survival.…”
mentioning
confidence: 99%
See 2 more Smart Citations